ABOUT THE PROBLEMS OF LIFE CRISIS OF PERSONALITY - Inesa V. Harkusha; Serhii V. Dubinskyi (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article provides a theoretical psychological analysis of the problem of life crisis of an individual, namely the concepts and manifestations of life crisis. In particular, the essence of the terms «crisis», «crisis of life» in the works of Ukrainian and foreign scientists has been studied. The following types of crises are distinguished: crises of mental development; age crises; crises of a neurotic nature; occupational crises; critical and semantic crises; life crises, crises of personality formation. health crises, terminal crises, crises of meaningful relationships, crises of personal autonomy, crises of self-realization, crises of life mistakes. It is noted that the crisis can be defined as a long-term internal conflict over life in general, its meaning, main goals and ways to achieve them. It is substantiated that different conceptual directions in their unity form a complex, multilevel system, which is a methodological basis for studying such a complex and interesting phenomenon as the life crisis. In the process of studying the problem of life crisis, such concepts as a «personal crisis», «psychological crisis», «psycho-spiritual crisis», «biographical crisis», «crisis of professional development» and others were introduced. It is established that the causes of crisis phenomena are observed in those people who, in the opinion of the environment, are quite prosperous in terms of ordinary ideas about happiness. It is also noted that the life crisis has a number of features that distinguish it from other emotionally complex life situations. It is emphasized that the life crisis can be of different depth and have several stages or levels, the passage of which has its own specific features. However, it is noted that the crisis is always accompanied by stress, in some way contains frustration and always requires the activation of value and meaning. It is stated that in the framework of crisis psychology two more features of the crisis of life as an event in the life of an individual should be noted.